Hydroxy-assisted regio- and stereoselective synthesis of functionalized alkenes via phosphine-catalyzed β′-umpolung addition of o-hydroxy aromatic aldimines to allenoates. Issue 15 (6th July 2018) - Cheng, Kunpeng; Bao, Yishu; Wang, Jiahua; Dai, Zonghao; Lu, Jinrong; Zhou, Qingfa
Abstract : An unprecedented β′-umpolung addition of o -hydroxy aromatic aldimines with allenoates has been developed under the catalysis of phosphine. Abstract : An unprecedented β′-umpolung addition of o -hydroxy aromatic aldimines with allenoates has been developed under the catalysis of phosphine. The reaction provides an efficient approach to the synthesis of functionalized alkenes in moderate to good yields with high stereoselectivities under mild conditions. The asymmetric version of this β′-umpolung addition has also been studied using chiral phosphines.